PENGEMBANGAN BUKU CERITA BERGAMBAR INTERAKTIF BERBASIS TRI HITA KARANA UNTUK PENDIDIKAN LINGKUNGAN SEKOLAH DASAR - Gede Darma Yoga; Ni Nyoman Kurniawati; Komang Trisna Mahartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited availability of innovative and contextuallearning media that integrate local wisdom to foster environmental awarenessamong elementary school students. The research aimed to develop an interactivepicture storybook based on the Tri Hita Karana philosophy for the topic Aku PeduliLingkungan, as well as to determine its validity and practicality. This researchemployed the Research and Development (R&D) approach using the ADDIE model,consisting of Analysis, Design, Development, Implementation, and Evaluationstages. The product was validated by media, material, and language experts, whileits practicality was evaluated by elementary school teachers and Grade II students.Data were collected through observations, interviews, and questionnaires andanalyzed using descriptive quantitative and qualitative techniques. The findingsindicate that the developed interactive picture storybook is highly feasible forclassroom implementation. The media achieved very high validity scores frommedia experts (98.67%), material experts (98.00%), and language experts(98.67%). Practicality testing also demonstrated excellent results, with teacherresponses reaching 98.00%, student responses 98.07%, and an overall average of98.04%. These findings imply that the interactive picture storybook based on Tri HitaKarana is a valid and practical learning medium that can support contextual learning,strengthen environmental care character, and integrate Balinese local wisdom intoprimary education.Kata kunci: interactive picture storybook, Tri Hita Karana, environmental education,learning media, elementary school